How SEO Impacts on Websites Rank? - Chaudhary, Roshan Kumar (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
The Internet has become a daily part of our lives. Today’s most of the businesses are online. Internet businesses and marketing are going to be a future in the upcoming days. Now Search Engine Optimization (SEO) makes a big impact on online companies by affecting their websites. So, being ranked in the Google search result is too important to boost the company's growth. This research paper analyzes what factors impact websites to rank in Google search results. This paper makes us maintain the contents of our website and provides a clear idea of how the contents of the website are ranked in Google search results. For the large growth in internet business, organic traffic with organic search clicks is important. Out of the entire thing, our website's design structure is too much more important than how much user familiar is with our site.